Audiovisual Media in Efl Listening: A Meta-Analysis of 21st Century Learning Resources - Alfi Az Zuhriyah; Irmayani Irmayani (Insan Akademika Publications, 2025)
This meta-analysis evaluates the effect of audiovisual (AV) medium on improving listening ability of EFL students, by combining the results of 21 quantitative studies conducted between 2015 and 2025. From a total of 1,987 learners at various levels of education, it was found that AV media had a significant positive impact on listening comprehension, with a Cohen's d effect size of 0.78. The results of the analysis also showed that several moderating variables influenced the level of effectiveness. Younger students tended to benefit more, the use of videos with subtitles gave the best results, and the intervention duration between 4 and 8 weeks had the most significant impact. AV media applied in formal educational contexts showed more effective results than in informal learning. The validity of these findings was strengthened through heterogeneity tests, moderator analysis, and evaluation of possible publication bias. Overall, this study confirms that AV media is an effective learning tool in the modern era, helping to improve EFL listening skills, design better teaching strategies, increase student engagement, and expand access to various sources of language input